Common mental disorders in visual artists in South Africa: occurrence of symptoms and associated factors - Swart, A. T. (My University, 2024)
Background: Studies have reported an association between mental illness and creativity. However, there are no studies of the prevalence of common mental disorders (depressive, anxiety and substance use disorders) in visual artists in low- and middle-income countries, including South Africa. Aim: To determine the occurrence of symptoms of common mental disorders (CMD) amongst visual artists in South Africa, to compare this with findings in the general population, and to explore associations with various demographic factors. Setting: Online survey completed by 231 members of VANSA (Visual Arts Network of South Africa). Methods: A cross-sectional observational study screening for the occurrence of symptoms of CMD using the SAMISS questionnaire. Results: A positive screen for a possible CMD was found in 87% and a positive screen for a possible substance use disorder in 64%. Gender (female) and monthly income (<R10,000) were significantly associated with a positive screen for a common mental disorder. No other socio-demographic or COVID-19 related variables were significantly associated with the occurrence of symptoms of a CMD. No significant associations between socio-demographic or COVID-19 related variables were found with the occurrence of symptoms of a substance use disorder. Conclusion: A high occurrence of symptoms of CMD (87%) and substance use disorders (64%) exists in a sample of VANSA members with a significant association between female gender and lower income level (<R10 000) and symptoms of CMD. Contributions: Findings suggest that further research is warranted and highlights the need to strengthen mental health support by increasing government funding of organizations such as VANSA.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Psychiatry to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Mental disorders; South African artists; SDG-3: Good health and well-being